Increasing walking among older people: A test of behaviour change techniques using factorial randomised N-of-1 trials. Issue 3 (3rd March 2016) - Nyman, Samuel R.; Goodwin, Kelly; Kwasnicka, Dominika; Callaway, Andrew
Abstract : Objective: Evaluations of techniques to promote physical activity usually adopt a randomised controlled trial (RCT). Such designs inform how a technique performs on average but cannot be used for treatment of individuals. Our objective was to conduct the first N -of-1 RCTs of behaviour change techniques with older people and test the effectiveness of the techniques for increasing walking within individuals. Design: Eight adults aged 60–87 were randomised to a 2 (goal-setting vs. active control) × 2 (self-monitoring vs. active control) factorial RCT over 62 days. The time series data were analysed for each single case using linear regressions. Main outcome measures: Walking was objectively measured using pedometers. Results: Compared to control days, goal-setting increased walking in 4 out of 8 individuals and self-monitoring increased walking in 7 out of 8 individuals. While the probability for self-monitoring to be effective in 7 out of 8 participants was beyond chance ( p  = .03), no intervention effect was significant for individual participants. Two participants had a significant but small linear decrease in walking over time. Conclusion: We demonstrate the utility of N -of-1 trials for advancing scientific enquiry of behaviour change and in practice for increasing older people's physical activity.